Epicardial Coronary Arteries in Khat Chewers Presenting with Myocardial Infarction - Ahmed Al-Motarreb; Adel Shabana; Ayman El-Menyar (International Journal of Vascular Medicine)
Background. Khat chewing is a common habit in Yemen despite increased evidence of its negative impact on the cardiovascular system. Aims. We aimed to study the epicardial coronary arteries in khat chewers presenting with myocardial infarction (AMI). Materials and Methods. A descriptive, cross-sectional study was conducted between November 2008 and May 2009 in Yemen. AMI patients who underwent coronary angiogram were enrolled and divided into groups (gp): gp1 (diabetic and khat chewers), gp2 (khat chewers and nondiabetic), and gp3 (diabetic and non-khat users). Results. Of 347 AMI patients 63%, 21%, and 16% were in gp 2, 3, and 1, respectively. Khat chewers were younger in comparison to non-khat users. Group 3 patients were more likely to have multivessel disease, severe left anterior descending (LAD), right coronary artery (RCA) stenosis and total RCA, and left circumflex (Lcx) occlusion compared to other groups. Group 1 patients were more likely to have total LAD occlusion and severe Lcx lesions. In multivariate analysis, age, diabetes mellitus, and smoking were significant independent predictors for significant coronary artery lesions; however, khat chewing did not show such association. Conclusions. Coronary spasm is the main mechanism of AMI in khat chewers. The impact of our finding for risk stratification and management warrants further studies.